Huangkui Capsule Attenuates Lipopolysaccharide-Induced Acute Lung Injury and Macrophage Activation by Suppressing Inflammation and Oxidative Stress in Mice. (22nd September 2021) - Deng, Jinfang; He, Zhenpeng; Li, Xiuru; Chen, Wei; Yu, Ziwen; Qi, Ting; Xu, Shuangyi; Xu, Zhengxin; Fang, Lei
Abstract : Background . Huangkui capsule (HKC) comprises the total flavonoid extract of flowers of Abelmoschus manihot (L.) Medicus. This study aimed to explore the effects of HKC on lipopolysaccharide- (LPS-) induced acute lung injury (ALI) in mice and LPS-stimulated RAW 264.7 cells. Methods . Enzyme-linked immunosorbent assay, histopathology, spectrophotometry, and quantitative real-time polymerase chain reaction were used for the assessments. Statistical analysis was performed using a one-way analysis of variance. Results . LPS significantly increased lung inflammation, neutrophil infiltration, and oxidative stress and downregulated lung miR-451 expression. Treatment with HKC dramatically, reduced the total cell count in the bronchoalveolar lavage fluid (BALF), and inhibited myeloperoxidase activity in the lung tissues 24 h after LPS challenge. Histopathological analysis demonstrated that HKC attenuated LPS-induced tissue oedema and neutrophil infiltration in the lung tissues. Additionally, the concentrations of tumour necrosis factor- (TNF-) α and interleukin- (IL-) 6 in BALF and IL-6 in the plasma reduced after HKC administration. Moreover, HKC could enhance glutathione peroxidase and catalase activities and upregulate the expression of miR-451 in the lung tissues. In vitro experiments revealed that HKC inhibited the production of nitric oxide, TNF- α, and IL-6 in LPS-induced RAW 264.7 cells and mouse primary peritoneal macrophages. Additionally, HKC downregulated LPS-induced transcription of TNF -α and IL-6 in RAW 264.7 cells. Conclusions . These findings suggest that HKC has anti-inflammatory and antioxidative effects that may protect mice against LPS-induced ALI and macrophage activation.